Diseño de un sistema de iluminación, alimentado mediante generación fotovoltaica para el complejo deportivo la bombonerita - Haro Sánchez, Wilson Roberto (2019)
In this project research was developed the luminous technical study of the current system of the Sport Complex "La Bombonerita", which was determined that the level of illumination is inferior to that allowed by the norms; UNE-EN 12193: Lighting of sports facilities and UNE-EN 13201: Lighting of car parks. This is the reason for the design and analysis of two lighting systems based on conventional and LED technologies using the Dialux software. The results obtained from these simulations have allowed to establish that the lighting system that complies with these norms, is the one developed on the basis of LED technology. The same will be energized with a concentrated photovoltaic generation system, with an installed power of 7.2 kWp, distributed in 20 monocrystalline modules of 360 Wp and an efficiency of 18%, which in radiation conditions of 1000 W / m2 deliver 7 kW, the accumulation system will consist of 20 deep discharge batteries at 150 Ah / 12V, a 30 A / 240 V MPPT charge regulator and the 5 kW / 80-800V inverter. In conclusion, the use of luminaires with LED technology, allows to obtain an efficient lighting system, which together with the photovoltaic system will contribute to the environmental preservation.